2020
DOI: 10.1007/s00392-020-01681-2
|View full text |Cite
|
Sign up to set email alerts
|

31 days of COVID-19—cardiac events during restriction of public life—a comparative study

Abstract: Aims The coronavirus SARS-CoV-2 outbreak led to the most recent pandemic of the twenty-first century. To contain spread of the virus, many nations introduced a public lockdown. How the pandemic itself and measures of social restriction affect hospital admissions due to acute cardiac events has rarely been evaluated yet. Methods and Results German public authorities announced measures of social restriction between March 21st and April 20th, 2020. During this period, all patients suffering from an acute cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 20 publications
4
26
1
6
Order By: Relevance
“…While we found a similar reduction of around 20% for discretionary cardiovascular admissions during the Covid-19 lock-down period, the rate of unavoidable admissions remained unchanged. These findings are in line with a report from a single emergency department at the University Hospital Ulm (Germany) with a cohort of 94 patients [ 7 ]. They saw a reduction in patients presenting with NSTEMI but not other forms of cardiovascular events, including STEMI and out of hospital cardiac arrest.…”
Section: Discussionsupporting
confidence: 92%
“…While we found a similar reduction of around 20% for discretionary cardiovascular admissions during the Covid-19 lock-down period, the rate of unavoidable admissions remained unchanged. These findings are in line with a report from a single emergency department at the University Hospital Ulm (Germany) with a cohort of 94 patients [ 7 ]. They saw a reduction in patients presenting with NSTEMI but not other forms of cardiovascular events, including STEMI and out of hospital cardiac arrest.…”
Section: Discussionsupporting
confidence: 92%
“…This effect may have been caused by the more restrictive lockdown regulations in these two countries. However, the reduction in myocardial infarctions observed in our study was much higher than the 25% reduction found in a dedicated analysis of the German health insurance company DAK from April 2020 ( 32 ) and the 22% reduction for cardiac events in 2020 compared to the average of 2017 to 2019 reported from Ulm University Hospital ( 33 ).…”
Section: Discussioncontrasting
confidence: 85%
“…While an association between acute viral respiratory disease and subsequent cardiovascular events had been described for other diseases (e.g., influenza) [5,6], several centers reported a decline in hospital admissions for acute cardiovascular and cerebrovascular emergencies during the COVID pandemic [7][8][9][10][11][12][13][14][15][16][17][18][19]. Since acute cardiovascular and cerebrovascular diseases remain leading causes for morbidity and mortality, further investigation of this concerning trend is warranted to identify potential implications for both health-care professionals and regulators.…”
Section: Introductionmentioning
confidence: 98%